Kefir and its biological activities - Azizi, Nor Farahin; Kumar, Muganti Rajah; Yeap, Swee Keong; Abdullah, Janna Ong; Khalid, Melati; Omar, Abdul Rahman; Osman, Mohd. Azuraidi; Syed Mortadza, Sharifah Alawieyah; Alitheen, Noorjahan Banu (MDPI AG, 2021)
Kefir is a fermented beverage with renowned probiotics that coexist in symbiotic association with other microorganisms in kefir grains. This beverage consumption is associated with a wide array of nutraceutical benefits, including anti-inflammatory, anti-oxidative, anti-cancer, anti-microbial, anti-diabetic, anti-hypertensive, and anti-hypercholesterolemic effects. Moreover, kefir can be adapted into different substrates which allow the production of new functional beverages to provide product diversification. Being safe and inexpensive, there is an immense global interest in kefir’s nutritional potential. Due to their promising benefits, kefir and kefir-like products have a great prospect for commercialization. This manuscript reviews the therapeutic aspects of kefir to date, and potential applications of kefir products in the health and food industries, along with the limitations. The literature reviewed here demonstrates that there is a growing demand for kefir as a functional food owing to a number of health-promoting properties.